2017
DOI: 10.13005/ojc/330162
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CMC from Palm Midrib Cellulose as Stabilizer and Thickening Agent in Food

Abstract: The using of carboxymethyl cellulose (CMC) from palm midrib as stabilizer on ice-cream making is done in three steps. First step is isolation process of á-cellulose from palm midrib powder, FTIR analysis shows that the compound is a cellulose molecule. The second step is alkalization with isopropanol as the solvent, carboxymethylation with monochloroacetic acid, and neutralization with CH 3 COOH 90% then ethanol, methanol and aquadest are used for purification followed with centrifugation process and adding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
1
9
0
1
Order By: Relevance
“…The results of this analysis are consistent with the results of research conducted by Purnomo & Lestari (2010); Sapariyah (2011), and Sebayang & Sembiring (2017), which state that self-efficacy affects performance. High selfefficacy will achieve a better performance because the individual has a strong motivation, clear goals, stable emotions and abilities to successfully perform activities on behavior.…”
Section: First Hypothesis (H1)supporting
confidence: 90%
See 1 more Smart Citation
“…The results of this analysis are consistent with the results of research conducted by Purnomo & Lestari (2010); Sapariyah (2011), and Sebayang & Sembiring (2017), which state that self-efficacy affects performance. High selfefficacy will achieve a better performance because the individual has a strong motivation, clear goals, stable emotions and abilities to successfully perform activities on behavior.…”
Section: First Hypothesis (H1)supporting
confidence: 90%
“…This can occur because of the low self-efficacy that is owned by employees. Research by Purnomo & Lestari (2010); Sebayang & Sembiring (2017), states that self-efficacy has an effect on performance. Narsim (2008); Irmayati et al, (2015); Zhahzadi et al, (2014); Syardianto et al, (2014); and Widnyana (2015), found that motivation influences employee performance and motivation contribute to improving performance.…”
Section: The Effect Of Self Efficacy On Financial Management Employeementioning
confidence: 99%
“…Furthermore, it is used in semisolid dairy products, salad dressing, and fruit syrup as a thickener [ 183 , 184 , 185 ]. Nowadays, in fruit syrup or juice, CMC is used as a hydrogel (dewatering agent) to ensure food safety.…”
Section: Application Of Cmcmentioning
confidence: 99%
“…In ice cream, 0.5% CMC is used as a stabilizer to produce the best quality ice cream. CMC with medium viscosity enhances the texture quality and provides creamy mouthfeel via eliminating the over-crystal growth of lactose in cream [ 120 , 185 ]. In cocoa and acid milk drinks, CMC is often used for stabilizing the texture of drinks, preventing sedimentation and layer forming in drinks at low and high temperatures [ 130 ].…”
Section: Application Of Cmcmentioning
confidence: 99%
“…The process of delignification, bleaching, and purification in palm midrib sample will give white alphacellulose (Sebayang and Sembiring, 2017). From 75 grams of palm oil, midrib powder will give 19.77 grams of pure alpha-cellulose (it was assumed to be 26.36% of the initial mass).…”
Section: Introductionmentioning
confidence: 99%